(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this research paper I have tried to throw light on the residential construction industry in PCMC, Pune as overall industry is facing the challenges to achieve the quality of the work, meet the dead line of the project and more importantly complete the project within the specified budget as post covid the construction material cost has shoot up surprisingly high, so wastage or overconsumption of it should be avoided,